The relationship between spino-pelvic alignment and primary dysmenorrhea - Wang, Juehan; He, Xin; Zhu, Ce; Ding, Hong; Feng, Ganjun; Yang, Xi; Liu, Limin; Song, Yueming (Frontiers in Surgery, 2023)
Introduction Most women of reproductive age suffered from the primary dysmenorrhea (PD). Up to date, most studies on the etiology of dysmenorrhea focused on endocrine factors while ignored the effect of spino-pelvic bony anatomy on uterus. In this study, we innovatively shed light on the relationship between primary dysmenorrhea and sagittal spino-pelvic alignment. Materials and Methods 120 patients diagnosed with primary dysmenorrhea and a control group of 118 healthy volunteers were enrolled into this study. All subjects received the standing full-length posteroanterior plain radiography to evaluate the sagittal spino-pelvic parameters. The visual analog scale (VAS) was used to assess pain rating of primary dysmenorrhea patients. Analysis of variance (ANOVA) or Student's t test was performed to measure statistical significance between differences. Results There was a significant difference in pelvic incidence (PI), sacral slope (SS), lumbar lordosis (LL) and thoracic kyphosis (TK) between PD group and Normal group (P<0.05). Furthermore, in PD group, the PI and SS was significant different between mild pain group and moderate pain group (P<0.05) and there was a significant negative correlation between pain rating and SS. From the perspective of sagittal spinal alignment, the majority of PD patients were classified with Roussouly type 2, meanwhile most normal people were classified with Roussouly type 3. Conclusion Sagittal spino-pelvic alignment was related to primary dysmenorrhea symptoms. Lower SS and PI angles may contribute to a worsen pain in PD patients.